Length of Catheter Use After Hysterectomy as a Risk Factor for Urinary Tract Infection. Issue 6 (November 2018) - Karp, Natalie E.; Kobernik, Emily K.; Kamdar, Neil S.; Fore, Amanda M.; Morgan, Daniel M.
Abstract : Objectives: The aims of this study were to determine the effect of length of postoperative catheterization on risk of urinary tract infection (UTI) and to identify risk factors for postoperative UTI. Methods: This was a retrospective case-control study. Demographic and perioperative data, including duration of indwelling catheter use and postoperative occurrence of UTI within 30 days of surgery, were analyzed for hysterectomies using the Michigan Surgical Quality Collaborative database. Catheter exposure was categorized as low—no catheter placed/catheter removed the day of surgery, intermediate—catheter removed postoperative day 1, high—catheter removal on postoperative day 2 or later, or highest—patient discharged home with catheter. A multivariable logistic regression model was developed to identify factors associated with UTI. An interaction term was included in the final model. Results: Overall, UTI prevalence was 2.3% and increased with duration of catheter exposure (low: 1.3% vs intermediate: 2.1% vs high: 4.1% vs highest: 6.5%, P < 0.0001). High (odds ratio [OR] = 2.54 [1.51–4.27]) and highest (OR = 3.39 [1.86–6.17]) catheter exposure, operative time (OR = 1.15 [1.03–1.29]), and dependent functional status (OR = 4.62 [1.90–11.20]) were independently associated with UTI. Women who had a vaginal hysterectomy with sling/pelvic organ prolapse repair were more likely to have a UTI than those who had a vaginal hysterectomy alone (OR = 2.58 [1.10–6.07]) and more likely to have a UTI than women having an abdominal or laparoscopic hysterectomy with a sling/pelvic organ prolapse repair (OR = 2.13 [1.12–4.04]). Conclusions: Length of catheterization and operative time are modifiable risk factors for UTI after hysterectomy. An interaction between vaginal hysterectomy and concomitant pelvic reconstruction increases the odds of UTI.